PHOTOPERIODIC MODULATION OF CIRCADIAN PROTEIN RHYTHM IN THE SILK GLAND OF BOMBYX MORI DURING FOURTH INSTAR DEVELOPMENT - B. SAILAJA; S. SIVAPRASAD (The Bioscan, 2010)
Circadian changes in the silk gland protein profiles were assayed in the fourth instar larva of Bombyx mori, under 12 h light and 12 h dark cycle (LD), continuous light (LL) and continuous dark (DD) conditions. The free running time of the protein rhythm, projected in the form of phase response curves shows characteristic peaks (elevated points) and troughs (low points) that presumably represent translation and transcription phases of the silk gene expression. The curves were further analyzed, in terms of the mean number of peaks and troughs and the interval between them with a view to determine the total number of protein synthetic cycles and the mean time required for the completion of each cycle (peak time + trough time), during the 24h-free running time or tau of the rhythm. Under LD and LL conditions, the protein rhythm followed a 24h cycle with 8 rounds of protein synthetic phases, each one being repeated at an interval of 2.9h. But under DD condition, the rhythm included 7 rounds of synthetic phases that are repeated every 3.3h. Obviously, the light condition under LD and LL, maintains the normal 24h protein rhythm while the dark condition under DD delays it by 3h and 12m.